New Records of Tortricid Moths (Lepidoptera, Tortricidae) from Ukraine - Kavurka, V.V. (Вестник зоологии, 2010)
Five species of tortricid moths of the tribe Grapholitini are recorded from Ukraine for the first time: Cydia oxytropidis (Martini, 1912); Pammene ignorata Kuznetzov, 1968; Dichrorampha teichiana Sulcs et Kerppola, 1997; Dichrorampha sylvicolana Heinemann, 1863 and Dichrorampha baixerasana Trematerra, 1991. Most of these species were collected in north-eastern regions of Ukraine. Впервые для фауны Украины указаны 5 видов листоверток, относящихся к трибе Grapholitini: Cydia oxytropidis (Martini, 1912), Pammene ignorata Kuznetzov, 1968, Dichrorampha teichiana S6ulcs et Kerppola, 1997, Dichrorampha sylvicolana Heinemann, 1863, Dichrorampha baixerasana Trematerra, 1991. Большинство этих видов собрано в северо-восточных регионах Украины